Supplier procedure in construction company: Alshem Group (M) Sdn Bhd / Ruzanna Ahmad Fuad - Ahmad Fuad, Ruzanna (2009)
ALSHEM GROUP (M) SDN BHD was incorporated in Malaysia in 1999.The company has since developed into a leading infrastructure and civil construction contractor. The company has undertaken a number of major infrastructure and civil construction works in the building industry throughout Malaysia. The company has also managed to secure and complete major civil engineering and building construction works in various disciplines and capabilities. The aim of this study is to view various criteria used to select the best supplier firm providing the most satisfaction for the criteria determined. This paper looks at various options in selecting the criteria of the supplier chosen. This report explains and reveal that there are various elements contribute to the supplier selection criteria stated by Nydick and Hills (1992) and strategies implemented by the company practices. Further studies and analysis should be undertaken and are recommended for alternative solution for ALSHEM GROUP (M) SDN BHD to select the best supplier for the company. The objective of supplier selection is to identify suppliers with the highest potential for meeting a firm's needs consistently and at an acceptable cost. To select prospective suppliers, the firm judges each supplier's ability to meet consistently and cost effectively its needs using selection criteria and appropriate measures. Even though there are no significant problems occurred, it certainly would help the company to be more secured if the supplier selection decision is made according to approach applied by Nydick and Hills (1992).